The nonlinear effect of debt on firm performance: the evidence from Indonesia - Raharja, Bayu Sindhu; Mranani, Muji (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research posits the nonlinearity model of capital structure in Indonesia by examining the rate of debt acquisition and its effect on firms’ performance. It uses the total debt and earnings after tax (EAT) as proxies of firms' performance from a sample of 2,064 as listed on the Indonesian Stock Exchange (IDX) from 1999 to 2018. To analyse the nonlinear effect, it uses the polynomial regression analysis. The results established the positive quadratic impact of debt on firms’ performance which predicts that increasing debt will trigger such high performance. It is conceived that increasing debt use in financing decisions will cause the company performance to go down in the future. This research provides a new perspective to the field of capital structure theory, especially to the classical trade-off theory. For future research, introducing other proxies in gauging firms’ performance may strengthen the validity of this study. It should also explain and elaborate on the nexus between debt increment and positive quadratic effect on firms’ performance, and also provide solutions to practical issues in the economy.